Space types and service capacity of stadiums - Zhong, X.; Wang, R.; Duan, H. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Service capability refers to the service conditions and standards of these services as provided by service system organizations. Stadiums and the associated facilities are a service place or service resource. Converting stadium service resources into service products in the presence of the capacity of a stadium is a challenge. Stadiums services (building) and space, as part of the sports service products` tangible resources, the process involved in sports service; the limitations of the type of services space and constraints of the layout supply. Methods Through literature review, field surveys and other methods, the perspective of services management, the relations between services processes and the characteristics of stadia and the stadiums space characteristics were investigated. The constraints and influencing factors with respect to space on the type of service and capacity to improve the sports facilities from the perspective of space design and the structure and layout to improve the function of stadiums and their effectiveness are discussed. Results / Discussion The impacts of a stadium`s service capabilities are determined by many factors. The construction site and the urban traffic conditions determine the service radius of the stadium, the space and types of services provided. The type of product, the level of technical design of venues and service facilities determine the service procedure and ultimately affect the quality of service. Facilities management and operational systems including the service resources development, product design services, facilities maintenance, security and other services are multifaceted, The influence of the capacity of the stadium, the residents personal awareness of the sports, and the knowledge and content of sports activities may affect the sports venues and the attractiveness of the service products. A stadiums services products, have both standardized services for the public, and customized services for individuals and interacting services under the guidance of professionals. Customers experience arec influenced by watching or participation in the competitions and performances, fitness and entertainment, sports and other recreational services.